If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.60X + 0.5(10 + -1X) = 0.10(-39) 0.60X + (10 * 0.5 + -1X * 0.5) = 0.10(-39) 0.60X + (5 + -0.5X) = 0.10(-39) Reorder the terms: 5 + 0.60X + -0.5X = 0.10(-39) Combine like terms: 0.60X + -0.5X = 0.1X 5 + 0.1X = 0.10(-39) Multiply 0.10 * -39 5 + 0.1X = -3.9 Solving 5 + 0.1X = -3.9 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 0.1X = -3.9 + -5 Combine like terms: 5 + -5 = 0 0 + 0.1X = -3.9 + -5 0.1X = -3.9 + -5 Combine like terms: -3.9 + -5 = -8.9 0.1X = -8.9 Divide each side by '0.1'. X = -89 Simplifying X = -89
| 5-n=-8n | | -2z+8=21+4z | | x-1*x-1= | | y-1=2y-1 | | 12z+6=z-1 | | 8x-40=20x-4 | | 6x+5.5=x+11 | | -17=10u | | 124-7x=11x+18 | | 287-4x=41x+22 | | 6-9x=47-16x | | -x^4+x^3+6x^2-14x+12=0 | | -x^5+3x^4+4x^3-26x^2+40x-24=0 | | m^3+2m-15=0 | | 5x+1=14x-82 | | 8x+4=16-9x | | (x-6)(2x+3)=0 | | 4x^2+22x=-16 | | 8x-12=52 | | 2x+6=x+19 | | 9x-23=58 | | 24x^4-54x=12x^3-27x | | 24x^4-54x^2-12x^3+27x=0 | | 156-3x=6x+21 | | 35-3c=6c+3.5 | | 12-2h=14h-36 | | 107-5x=22x+20 | | 8g-9=5g+12 | | 4p-3=2p+9 | | 109-7x=11+17 | | 3n+5=8n+1 | | 2m+7=3m-18 |